Pengaruh Pengungkapan Corporate Social Responsibility, Ukuran Perusahaan, dan Leverage terhadap Nilai Perusahaan dengan Profitabilitas sebagai Variabel Mediasi - Yuliana Yuliana; Mar’atus Solikah; Andy Kurniawan (Moneter : Jurnal Ekonomi dan Keuangan, 2026)
This study is intended to examine the effect of Corporate Social Responsibility (CSR), firm size, and leverage on firm value, with profitability as a mediating variable in manufacturing companies listed on the Indonesia Stock Exchange during the 2023-2025 period. This research employs a quantitative approach using secondary data obtained from company annual reports. The sample selection was carried out using a purposive sampling technique. The analytical method used is path analysis, processed with the assistance of the SPSS software, while mediation testing is conducted using the bootstrapping method. The results indicate that Corporate Social Responsibility (CSR), Firm Size, and Leverage have a significant effect on Firm Value. Meanwhile, Corporate Social Responsibility (CSR), Firm Size, and Leverage do not have a significant effect on Profitability, and Profitability does not have a significant effect on Firm Value. Furthermore, the mediation test results reveal that Profitability is unable to mediate the effect of Corporate Social Responsibility (CSR), Firm Size, and Leverage on Firm Value. Therefore, an increase in firm value is not solely determined by profitability, but is also influenced by other factors such as Corporate Social Responsibility (CSR), Firm Size, and Leverage.